Pengaruh Faktor-faktor Stres Kerja Karyawan Terhadap Prestasi Kerja Karyawan pada PT. Pos Indonesia (Persero) Kantor Area II Padang - Indria, Vivi; Dewita Hia, Yulna; Natassia, Rizky (Pendidikan Ekonomi, 2014)
ABSTRACT Â This research is motivated by the influence of stress in the work environment factors , organizational factors and individual factors on employee performance on PT.Pos Indonesia ( Persero ) Area II Office of Padang . This study aims to determine the influence of environmental factors , organizational factors and individual factors on employee performance on PT.Pos Indonesia ( Persero ) Area II Office of Padang .This research is a descriptive study associative . The population in this study were all employees of PT . Pos Indonesia ( Persero ) Area II Office of Padang . The sampling technique used is total sampling . Analysis tools used are validity , reliability test , normality test, multicollinearity , multiple linear regression , t test , F test , and test the coefficient of determination ( R2 ) .The results of this study are : a significant difference between occupational stress factors with employee performance PT.Pos Indonesia ( Persero ) Area II Office of Padang . T value to variable environmental factors 2.918 > t table value 1.671 , t value variable organizational factors at 4.464 > t table value of 1.671 , and the t value variable individual factors t value 4.241 > t table value of 1.671 , and the coefficient of determination ( R2 ) of 0.752 .Based on these results , it is advisable for the company considering the factors such as job stress causes environmental factors , organizational factors such as the work load as well as individual factors such as family problems or innate characteristics .